D-Dimer as Predictor of Large Vessel Occlusion in Acute Ischemic Stroke. Issue 3 (10th February 2021) - Ramos-Pachón, Anna; López-Cancio, Elena; Bustamante, Alejandro; Pérez de la Ossa, Natàlia; Millán, Mònica; Hernández-Pérez, Maria; Garcia-Berrocoso, Teresa; Cardona, Pere; Rubiera, Marta; Serena, Joaquín; Ustrell, Xavier; Garcés, Moisés; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Improving prehospital triage of large vessel occlusion (LVO) would reduce time to reperfusion therapies. We aimed to study early predictors of LVO in acute ischemic stroke to identify candidates for endovascular treatment. Methods: The Stroke-Chip was a prospective observational study conducted at 6 Stroke Centers in Catalonia. Blood samples were obtained in the first 6 hours from symptom onset of consecutive patients. Stroke severity was evaluated with National Institutes of Health Stroke Scale (NIHSS) and LVO was assessed. Independent association of multiple blood biomarkers with LVO was evaluated using logistic regression models adjusted by covariates. Sensitivity, specificity, and predictive values were assessed for NIHSS and the combination of NIHSS and selected serum biomarkers levels. Results: One thousand three hundred eight suspected strokes were enrolled for a 17-month period. LVO was not assessed in 131 patients. One thousand one hundred seventy-seven patients were selected for analysis (mean age 69.3 years, 56% men, median baseline NIHSS of 6, and median time to blood collection 2.5 hours). LVO was detected in 262 patients. LVO patients were older, had higher baseline NIHSS, history of atrial fibrillation, and lower time from stroke onset to admission. After logistic regression analysis, D-dimer remained an independent predictor of LVO (odds ratio, 1.59 [1.31–1.92]). Specificity and positive predictive value to exclude or detect LVO were higher when using combined D-dimer levels and NIHSS score assessment rather than NIHSS alone. Conclusions: Early D-dimer levels are an independent predictor of LVO and may be useful to better optimize prehospital patient transport to the appropriate stroke center.